Juridical Analysis for the Rights of Interested Third Parties in Filing Pretrial Applications in the Indonesian Criminal Justice System - Fahrizal S. Siagian (IHSA Institute, 2023)
Law enforcement is often faced with procedural errors by its law enforcement officials. Pretrial is an institution for supervising criminal procedural law enforcement so that nothing conflict with the principle of presumption of innocent. The Problem Formulation of this research about how is the Right of Interested Third Parties Filing Pretrial Applications in the Indonesian Criminal Justice System? how is the correlation between the Criminal Procedure Code and Constitutional Court Decision Number 76/PUU-X/2012 concerning the Results of the Review of Pretrial Authority of Interested Third Parties? The purpose of this study is solely to obtain answers to both problem formulations. The research method is a normative legal research method referring to legislation and court decisions using secondary data, namely primary, secondary and tertiary legal materials. Data collection by Library Research. All data is processed by descriptive analysis. The results of this study are first known that the Rights of Interested Third Parties in judicial practice are still lacking and this is because the Criminal Procedure Code does not specify that Interested Third Parties can apply for Pretrial. Second The Constitutional Court has made it clear specifically that interested third parties can still apply for pretrial with the aim that everyone has the right to social control. Pretrial has been strengthened by the existence of the Criminal Procedure Code and the Constitutional Court Decision as legal standing that proves that anyone who is considered interested with strong reasons can apply for pretrial in order to achieve justice, certainty and legal expediency.